SOUZA, Donaldo Bello de; MARTINEZ, Silvia Alicia (org.). Livro - Educação Comparada: rotas de além-mar. São Paulo: Xamã, 2009 - Vendrame, Fernando (InterMeio: Revista do Programa de Pós-Graduação em Educação - UFMS, 2017)
.